2022
DOI: 10.3389/fnut.2022.823039
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Derived From Beetroot Juice Lowers Blood Pressure in Patients With Arterial Hypertension: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlthough there are a considerable number of clinical studies on nitrate (NO3) rich beetroot juice (BRJ) and hypertension, it is difficult to indicate the real effects of NO3 from BRJ on the BP of hypertensive patients because there are still no estimates of the effects of NO3 derived from BRJ on the BP of hypertension patients.ObjectiveTo clarify these effects, we developed a systematic literature review with a meta-analysis of randomized clinical trials (RCTs).DesignThe searches were accomplished th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
(96 reference statements)
0
13
1
1
Order By: Relevance
“…The number of participants in this study considered the most recent meta-analysis study, which found a reduction of 5 mmHg caused by beetroot juice rich in nitrate in patients with SAH as significant with a variation of 4 mmHg [ 10 , 11 ]. We applied these values in the Hedwig Harvard Sample Calculator software online, considering a bilateral 95% confidence interval and a power analysis of 80% that provided a minimum of 11 participants for this clinical trial [ 29 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of participants in this study considered the most recent meta-analysis study, which found a reduction of 5 mmHg caused by beetroot juice rich in nitrate in patients with SAH as significant with a variation of 4 mmHg [ 10 , 11 ]. We applied these values in the Hedwig Harvard Sample Calculator software online, considering a bilateral 95% confidence interval and a power analysis of 80% that provided a minimum of 11 participants for this clinical trial [ 29 ].…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…In addition to the previously described exogenous pathway, NO can also be synthesized endogenously via the l-arginine + O2 pathway, mediated by NO-synthase enzymes [9]. Recent meta-analyses of clinical trials have shown that NO3 consumed through beetroot juice lowers blood pressure more clearly [10,11] than in its salt form (e.g., sodium/ potassium NO3) [12]. There are assumptions that this occurs through the interaction between NO3 and the vitamins, minerals, and phenolic compounds present in beet juice, generating more intense pressure and vascular responses [10].…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the compounds in beetroot (Beta vulgaris L.), betaine and nitrate have demonstrated promising results on cardiovascular activity 1,2 . Such compounds are able to optimize cardiovascular parameters (e.g., blood pressure and heart rate), both in healthy populations in addition to the cardiovascular diseases (e.g., hypertension, coronary heart disease) [3][4][5] . Of late, some studies have stated that compounds in beetroot can interact and optimize cardiac autonomic control 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Through digestive processes, nitrite is further reduced to nitric oxide (NO) which subsequently enters systemic circulation. Circulating NO becomes bioactive in tissues and blood primarily under conditions of hypoxia, and can influence blood vessel vasodilation, mitochondrial respiration, and muscle contractile function [45,46].…”
mentioning
confidence: 99%